Financial Performance Assessment Of The First Private Auto Parts Company In Indonesia Based On Ratio Analysis - Masno Marjohan; Sugiyanto Sugiyanto (universitas Pamulang, 2022)
Objective: This study aims to determine the effect of liquidity (CR) and NPM on the profitability (ROA) of auto parts companies listed on the Indonesia Stock Exchange for the period 2011 – 2020. Methodology: This study adopts a quantitative descriptive methodology, collecting financial statements of companies that have been listed on the IDX. The measurement model and hypothesis testing were carried out using SPSS software. .Findings: The results show that the Current Ratio has no significant effect on Return on Assets Net Profit Margin has a significant effect on Return on Assets and the Current Ratio and Net Profit Margin simultaneously have a significant effect on Return On Assets. Conclusion: Assessment of financial performance at auto parts companies simultaneously has a significant effect on Return on Assets and partial Net Profit Margin has a significant effect on Return on Assets while the Current Ratio has no significant effect on Return on Assets